Impacts of local characteristics on regional FDI inflows into Mekong Delta - Nguyen Kim Phuoc (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration, 2016)
The study used theory from Keynes (1936), Dunning (1981), Heckscher & Ohlin (1991) on the movement of capital and foreign investment in previous studies, which are related to FDI to platform scientific research proposed model. GMM regression methods were used to determine the impacts of the 15 independent variables (including 6 variables representative for local characteristics) to FDI inflows (the dependent variable) in the Mekong Delta. Results found 9/15 variables affecting FDI flow into the Mekong Delta, which has 3 variables representing local characteristics: Regular expenses, freight volume by water and by land. Based on the results of research and local characteristics, some recommendations are proposed to attract FDI into more Mekong Delta.